2020
DOI: 10.1001/jamanetworkopen.2020.19722
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Status and Other Clinical Characteristics With COVID-19 Test Results

Abstract: Key Points Question Is vitamin D status, reflecting vitamin D levels and treatment, associated with test results for coronavirus disease 2019 (COVID-19)? Findings In this cohort study of 489 patients who had a vitamin D level measured in the year before COVID-19 testing, the relative risk of testing positive for COVID-19 was 1.77 times greater for patients with likely deficient vitamin D status compared with patients with likely sufficient vitamin D status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
419
3
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 452 publications
(460 citation statements)
references
References 29 publications
24
419
3
14
Order By: Relevance
“…Growing evidence supports a link between vitamin D and COVID-19. The first reports indicated that adults with hypovitaminosis D were at greater risk of being infected with SARS-CoV-2 (relative risk 1.77 with p < 0.02), [11] and that cases with COVID-19 had lower 25(OH)D concentrations compared to controls without COVID-19 (respectively, 11.1 ng/mL versus 24.6 ng/mL, p = 0.004) [12]. Similarly, significant inverse correlations were found in 20 European countries between the mean serum 25(OH)D concentrations and the number of COVID-19 cases, as well as with mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports a link between vitamin D and COVID-19. The first reports indicated that adults with hypovitaminosis D were at greater risk of being infected with SARS-CoV-2 (relative risk 1.77 with p < 0.02), [11] and that cases with COVID-19 had lower 25(OH)D concentrations compared to controls without COVID-19 (respectively, 11.1 ng/mL versus 24.6 ng/mL, p = 0.004) [12]. Similarly, significant inverse correlations were found in 20 European countries between the mean serum 25(OH)D concentrations and the number of COVID-19 cases, as well as with mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the analysis of the role of cellular organelles and substances that are directly involved in the regulation of oxidative stress is essential [5,6]. It is well-described that the antioxidant effects of vitamin D may be very useful in the prevention and attenuation of COVID-19 symptoms, and that a deficient vitamin D status would confer susceptibility to morbidity and mortality by SARS-CoV-2 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent large UK Biobank study, after adjustment for confounding factors, did not show correlations between the serum vitamin D levels and the risk of COVID-19 infection [21]. On the contrary, other series reported a higher prevalence of 25OH-vitamin D deficiency in patients with a COVID-19 positive test [22][23][24]. Of note, in these studies a significant timeframe between the serum Vitamin D sample collections and COVID-19 infection elapsed (up to 12 months), which may produce a bias, whereas all the three groups of our study collected the 25OH-Vitamin D blood sample on admission to hospital.…”
Section: Discussionmentioning
confidence: 98%